Identification of stable pollen development related reference genes for accurate qRT-PCR analysis and morphological variations in autotetraploid and diploid rice. - Jinwen Wu (Public Library of Science (PLoS), 2021)
Autotetraploid rice exhibited hybrid vigor and greater genetic variation compared to diploid rice, but low pollen fertility is a major hindrance for its utilization. Our previous analysis revealed that large number of pollen fertility genes were exhibited down-regulation in autotetraploid rice. Hence, it is of utmost importance to reveal the expression patterns of pollen fertility genes with high accuracy. To find stable reference genes for autotetraploid rice, we compared the pollen development stages between diploid and autotetraploid rice, and 14 candidate genes were selected based on transcriptome analysis to evaluate their expression levels. Autotetraploid rice (i.e. Taichung65-4x) displayed lower seed set (40.40%) and higher percentage of abnormalities during the pollen development process than its diploid counterpart. To detect the candidate reference genes for pollen development of autotetraploid and diploid rice, we used five different algorithms, including NormFinder, BestKeeper, ΔCt method, geNorm and Re-Finder to evaluate their expression patterns stability. Consequently, we identified two genes, Cytochrome b5 and CPI, as the best candidate reference genes for qRT-PCR normalization in autotetraploid and diploid rice during pre-meiosis, meiosis, single microspore and bicellular pollen development stages. However, Cytochrome b5 was found to be the most stably expressed gene during different pollen development stages in autotetraploid rice. The results of our study provide a platform for subsequent gene expression analyses in autotetraploid rice, which could also be used in other polyploid plants.